"Accept and Utilize": Alternative Medicine, Minimality, and Ethics in an Indonesian Healing Collective. (28th May 2018) - Long, Nicholas J.
Abstract: Cosmopolitan forms of alternative medicine have become very popular in contemporary Indonesia. Many healers have trained in an eclectic range of techniques, predicated on ontological claims so diverse that they call each other's legitimacy into question. This article explores how a collective of alternative healers in central Java navigated the quandaries presented by such therapeutic eclecticism over a six‐year period. Healers' engagement with, or indifference toward, the principles underpinning therapeutic efficacy fluctuated in ways that allowed them to surmount the dilemmas of Islamization, the changing demographic of their collective's membership, and the threat of commercialization, thereby maintaining a medical landscape in which alternative healing was widely available and accessible. Transformations in their understanding, experience, and practice of healing should thus be understood in terms of how enduring ethical commitments are refracted through ongoing engagements with a changing social world.